2020
DOI: 10.1111/hepr.13582
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma after Fontan surgery: A systematic review

Abstract: Aim: Fontan surgery is often the procedure of choice for patients with congenital single effective ventricle. In the long term, elevated systemic venous pressure and chronic ischemia following this procedure could lead to advanced chronic liver disease and there is also a risk of hepatocellular carcinoma (HCC). This review systematically summarizes the characteristics and outcomes of this rare condition. Methods: PubMed and Embase databases were searched from inception to January 2020 for studies reporting on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…In patients with FALD-HCC, liver transplantation and hepatectomy are generally very difficult due to a poor cardiac function and three to four times higher systemic venous pressure than in normal patients (9). Several reports have demonstrated that TACE was useful for the treatment of FALD-HCC, so we did consider performing TACE (2,4,9). In general, the presence of systemic-topulmonary venous shunt may cause unexpected embolism due to the embolic material used in TACE, as described in a previous case report of post-TACE cerebral infarction and retinal artery occlusion in a patient with FALD-HCC (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with FALD-HCC, liver transplantation and hepatectomy are generally very difficult due to a poor cardiac function and three to four times higher systemic venous pressure than in normal patients (9). Several reports have demonstrated that TACE was useful for the treatment of FALD-HCC, so we did consider performing TACE (2,4,9). In general, the presence of systemic-topulmonary venous shunt may cause unexpected embolism due to the embolic material used in TACE, as described in a previous case report of post-TACE cerebral infarction and retinal artery occlusion in a patient with FALD-HCC (13).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to significant advances in paediatric cardiology, the number of long-term survivors without cyanosis has increased. In these patients, haemodynamic changes that occur during a prolonged lifespan often develop into pathological conditions, such as chronic heart failure and Fontan-associated liver disease (FALD), including liver cirrhosis (LC) and hepatocellular carcinoma (HCC) (2,3). In patients with FALD, hepatic congestion and systemic hypoxia caused by chronic heart failure and systemic-to-pulmonary shunt enhance hepatic fibrogenesis, which is one of the main risk factors for HCC (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the time since surgery, patients who have undergone a Fontan procedure are at risk of developing gastrointestinal and liver complications, including advanced liver fibrosis, cirrhosis, hepatocellular carcinoma, portal hypertension, protein-losing gastroenteropathy, and GEVs [ 5 15 , 17 , 18 , 30 , 31 ]. As these complications significantly influence patients’ quality of life after the surgery, numerous efforts have been made to develop and establish non-invasive and accurate methods or parameters to screen for them [ 7 , 17 , 32 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the prognosis of HCC-related to Fontan procedure is poor (1-year survival around 50%) and the management and surveillance of patients has to be improved. 85 , 94 Recently, the American Heart Association published new guidelines for the surveillance of the patients and a bi-annual screening for HCC should be proposed once the diagnosis of cardiac cirrhosis is established 21 ( Table 2 ).…”
Section: Surveillance and Hepatocellular Carcinoma Occurrencementioning
confidence: 99%